Alterações cardiorrespiratórias em sujeitos com distúrbios respiratórios e aumento da circunferência abdominal submetidos à sessão única de fisioterapia respiratória - Martinelli, Bruno (2016)
The knowledge about the influence of obesity on the respiratory system is complex and goes beyond the physical and mechanical effects, this is also related to autonomic, metabolic and inflammatory disorders. Obesity can overload the respiratory system through multiple mechanisms with imposition and mechanical restrictions beyond the release of circulating factors of fat storage. Respiratory therapy modifies the cardiorespiratory and thoracoabdominal mechanisms, however there is little evidence about its impact on abdominal obesity. Thus, this thesis consisted of two studies. The first study was titled by "Cardiorespiratory responses according to measurement of abdominal circumference (AC) in men with obstructive ventilatory disturbance undergoing chest physical therapy". The aim of this study was to compare the cardiorespiratory effects among men with obstructive ventilatory disturbance according to the measure of AC submitted to respiratory physiotherapy. Twenty-six men with predicted Forced expiratory volume in the first second and Forced Vital Capacity <70% were divided into 2 groups according to the AC (cm): <102 (ACwithout_risk) and >102 (ACrisk). The heart rate variability (HRV), peripheral oxygen saturation, blood pressure, lung volumes and flows, maximum expiratory pressure were measured at rest, immediately after physiotherapy intervention - which consisted of breathing exercises for airway clearance, active kinesiotherapy to lower and upper limbs, and after 30 minutes. The obese had higher age, anthropometric measurements and lower thoracoabdominal amplitude index. After the intervention they showed a higher percentage of inspiratory capacity, heart rate variability and diastolic blood pressure. Concluding, abdominal obesity limits thoracoabdominal expansibility and modifies the diastolic blood pressure, but the respiratory therapy promotes improvement in cardiac autonomic modulation and eutrophic subjects benefit more to respiratory and cardiac measures. The second study was titled by “Cardiorespiratory repercussions of the only chest physical therapy in subjects with abdominal obesity and restrictive pulmonary disorders”. The aim of this study was to identify and compare the cardiac and respiratory effects among men with restrictive lung disease according to the AC undergoing a respiratory physiotherapy. Twenty-six men with predicted Forced Vital Capacity <80% were divided into 2 groups according to the AC (cm): <102 (ACwithout_risk), and >102 (ACrisk). The HRV, peripheral oxygen saturation, blood pressure, lung volumes and flows, maximum expiratory pressure were measured at rest, immediately after physiotherapy intervention - which consisted of breathing exercises for pulmonary expansion, active kinesiotherapy to lower and upper limbs, and after 30 minutes. The obese had higher measures of systolic blood pressure, slow vital capacity, inspiratory capacity, maximal expiratory pressure and expiratory flow rate at the 50% relative to the total volume; and the heart rate variability increased only after the intervention. Concluding, the men with restrictive respiratory disorder are benefited by respiratory physiotherapy improving heart and respiratory variables independently of the AC, however the sympathovagal modulation is modified only immediately after the intervention. As a general conclusion, it became clear that the subjects with abdominal obesity, independent of the associated respiratory disorders, had restrictive respiratory limitations caused by the adipose tissue and compensatory increase in inspiratory capacities, but these subjects tend to benefit from chest physical therapy intervention with increase of the HRV and others cardiac and respiratory measures, but to a lesser extent than the subjects with lower abdominal circumference. Spirometry measurements performed slowly and favoring the inspiration allow greater gain by the obese. However, the systemic arterial blood pressure levels are changed or rise, that may represent evidence of cardiovascular complications. Continue to investigate these relations, including in the long term, it will be one of the possibilities of the later studies.